ANALISIS PERBANDINGAN DEFLASI TORNIQUET LANGSUNG DAN BERTAHAP TERHADAP PERUBAHAN TEKANAN DARAH PADA PASIEN OPERASI TOTAL KNEE ARTHROPLASTY - Hidayah, Nurul; Nahariani, Pepin; Kholis, Anja Hesnia; Priyanti, Ratna Puji; Hidayat, Wahyu; Utomo, Azis Mualim Priyo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Arterial tourniquets are used in extremity surgical procedures to create a bloodless surgical field. In Total Knee Arthroplasty (TKA) there is redistribution of intravascular volume to the ischemic lower extremity, bleeding, and vasodilation, thereby potentially reducing arterial blood pressure. Objective: to analyze the differences in blood pressure reduction in TKA patients after direct and gradual tourniquet deflation. Methods: Using the Quasy experiment, the population was TKA surgery patients in the Central Surgery Room at Dr. RSUD. Soedono, East Java Province in January – March 2024. Using Simple Random Sampling techniques, it was found that n=24 respondents were divided into intervention group n=12 and control group n=12. Data analysis used the independent T-test. Results: There was no significant difference in pre-intervention systolic and diastolic blood pressure between the gradual and direct groups (p=0.055, p=0.451), there was no significant difference in post-intervention systolic blood pressure between the gradual and direct groups (p=0.578) and there was a significant difference diastolic blood pressure at post intervention between the gradual and immediate groups (p=0.032). The mean difference between pre and post systolic blood pressure in the gradual deflation group was 4.08 mmHg and Dyastole was 6.17 mmHg. Meanwhile, the difference in the mean value of pre and post Systole blood pressure in the direct deflation group was 19.31 mmHg and Dyastole was 10.55. The decrease in blood pressure in both systole and diastole in the gradual deflation group was smaller than in the immediate deflation group. Conclusion: Gradual tourniquet deflation allows for a smaller risk of lowering blood pressure than directly so it can be considered as an alternative method of tourniquet deflation after TKA surgery